Navigasi Kepemimpinan Di Era Digital: Tantangan Dan Peluang Bagi Generasi Milenial - Purnomo, Joko; Sri Pudjiarti, Emiliana (Transformasi: Journal of Economics and Business Management, 2024)
This paper explores the emerging leadership dynamics in the ever-evolving digital era, with a particular focus on the role of the millennial generation. Digital transformation has fundamentally changed the business and organizational landscape, giving rise to challenges and opportunities that tomorrow's leaders must face. The millennial generation, coming of age amidst the technological revolution, occupies a unique position in this context. They have high technology savvy, different values, and unique expectations for leadership. This paper will explore how millennials can face challenges such as adapting to rapid technological change, navigating evolving work cultures, and fulfilling their expectations for meaning in work. On the other hand, this paper will also discuss the opportunities available to the millennial generation in utilizing technology and their values ​​to lead teams and organizations effectively. Through an in-depth understanding of these changes, this paper aims to provide guidance for the millennial generation who want to succeed in leadership roles in the digital era that continues to transform.